Penerapan Senam Kaki dalam Asuhan Keperawatan Pasien dengan Diabetes Melitus - Dimas Prayoga; Hertuida clara (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2023)
Diabetes mellitus, a metabolic disorder, is a chronic disease distinguished by hyperglycemia (above-normal blood sugar levels). Case studies are conducted to gain practical experience in administering foot exercises and providing nursing care to clients with diabetes mellitus. The descriptive method was used, along with a case study approach and the use of evidence-based practices. Nursing care was provided to a 55-year-old female patient with diabetes and ketosis. The results of the study obtained four nursing problems, namely ineffective airway clearance, unstable blood glucose levels, risk of nutritional deficits, risk of ineffective peripheral perfusion. The implementation was carried out, namely doing diabetic foot exercises for 15-20 minutes with a frequency of 1x/day for three days to reduce tingling in patients. The evaluation results showed that the tingling sensation was significantly reduced on the third day. In conclusion, diabetic foot exercise can be applied to diabetes mellitus patients who experience impaired peripheral blood flow. Hopefully the results of this study can provide information about the application of diabetic foot exercises to patients and their families to reduce tingling in the feet.